2023
DOI: 10.1093/humrep/dead031
|View full text |Cite
|
Sign up to set email alerts
|

Linking human Dead end 1 (DND1) variants to male infertility employing zebrafish embryos

Abstract: STUDY QUESTION Is the vertebrate protein Dead end (DND1) a causative factor for human infertility and can novel in vivo assays in zebrafish help in evaluating this? SUMMARY ANSWER Combining patient genetic data with functional in vivo assays in zebrafish reveals a possible role for DND1 in human male fertility. WHAT IS KNOWN ALREADY About 7% of the male popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…A key component localized to these organelles is Dead end (Dnd1), a conserved vertebrate-specific RNA-binding protein that is essential for germline development. Loss of the protein can result in sterility and formation of germ cell tumors [14][15][16][17][18][19][20] and accordingly, recent work showed that germ cells with impaired Dnd1 function fail to maintain their totipotency and acquire somatic fates 21 . Despite the central role of Dnd1 in controlling the development of the vertebrate germline, the precise molecular function of the protein in the context of the phase-separated structures within which it resides is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…A key component localized to these organelles is Dead end (Dnd1), a conserved vertebrate-specific RNA-binding protein that is essential for germline development. Loss of the protein can result in sterility and formation of germ cell tumors [14][15][16][17][18][19][20] and accordingly, recent work showed that germ cells with impaired Dnd1 function fail to maintain their totipotency and acquire somatic fates 21 . Despite the central role of Dnd1 in controlling the development of the vertebrate germline, the precise molecular function of the protein in the context of the phase-separated structures within which it resides is unknown.…”
Section: Introductionmentioning
confidence: 99%